Role of mu opioid receptor (MOR) agonist efficacy as a determinant of opioid antinociception in a novel assay of pain-depressed behavior in female and male mice - Negus, S. Stevens; Akbarali, Hamid I.; Kang, Minho; Lee, Young K.; Marsh, Samuel A.; Santos, Edna J.; Zhang, Yan (Frontiers in Pain Research, 2023)
Intermediate efficacy mu opioid receptor (MOR) agonists have potential to retain analgesic effectiveness while improving safety, but the optimal MOR efficacy for effective and safe opioid analgesia is unknown. Preclinical assays of pain-depressed behavior can assess effects of opioids and other candidate analgesics on pain-related behavioral depression, which is a common manifestation of clinically relevant pain and target of pain treatment. Accordingly, the present study goal was to validate a novel assay of pain-depressed locomotor behavior in mice and evaluate the role of MOR efficacy as a determinant of opioid analgesic effects and related safety measures. Male and female ICR mice were tested in a locomotor chamber consisting of 2 compartments connected by a doorway that contained a 1-inch-tall barrier. Dependent measures during 15-min behavioral sessions included crosses between compartments (which required vertical activity to surmount the barrier) and total movement counts (which required horizontal activity to break photobeams in each compartment). Intraperitoneal injection of lactic acid (IP acid) produced a concentration-and time-dependent depression of both endpoints.Optimal blockade of IP acid-induced behavioral depression with minimal motor impairment was achieved with intermediate-efficacy MOR treatments that also produced less gastrointestinaltransit inhibition and respiratory depression than the high-efficacy MOR agonist fentanyl. Sex differences in treatment effects were rare. Overall, these findings validate a novel procedure for evaluating opioids and other candidate analgesic effects on pain-related behavioral depression in mice and support continued research with intermediate-efficacy MOR agonists as a strategy to retain opioid analgesic effectiveness with improved safety.